Factors associated with patient satisfaction in perioperative anesthesia care at Hawassa university comprehensive specialized hospital, Ethiopia. Cross-sectional study design. (2020) - Siraneh, Amanu Gashaw; Dendir, Getahun; Paulos, Kebreab
Abstract: Background: Patient satisfaction with perioperative anesthesia care represents an essential aspect of quality health care management. The assessment of patient satisfaction is a reality of practice today for good patient satisfaction with health care provider interaction and health influencing factors. Objectives: To assess the magnitude and associated factor of patient satisfaction towards anesthesia care at Hawassa university comprehensive specialized hospital. Method: A prospective cross-sectional study design was employed in an adult surgical patient scheduled for surgery under general anesthesia, and the regional anesthesia level of satisfaction and factors associated with satisfaction were analyzed. Data were entered into EPI- info version 7 and transferred to SPSS version 25.0 for analysis. Normality tests checked using the Shapiro-Wilk and Kolmogorov-Smirnov data were normally distributed. The frequency, percentage, and cross-tabulation with different variables were determined, finally, the magnitude and associated factors were analyzed by binary logistic regression and multivariate logistic regression. Variables P-value < 0.2 binary logistic regression included in a multivariate logistic regression and p-value < 0.05 was taken as statistically significant. Result: A total of 200patient were included in this study with a response rate of 100%. The main findings of this study were predictors of perioperative patient dissatisfaction were general anesthesia, duration of surgery, nausea, and vomiting, and pain after surgery. The magnitude of patient satisfaction was 60%. The odds of the patient who took general anesthesia were 2.31"(1.096, 4.142)" p = 0.026 more dissatisfied than regional anesthesia. The odds of the patient duration of surgery, 2–3hr 0.313 "(0.124, 0.792)" less likely dissatisfied than the duration of surgery 1hr.The odds of patient nausea and vomiting AOR = 2.575"(1.163, 5.698)" P = 002 more likely dissatisfied than did not have nausea and vomiting. The odds of patient pain after surgery AOR = 2.28"(1.084, 4.76)" more likely dissatisfied than the patient did not have pain after surgery. Conclusion: Patient satisfaction with perioperative anesthesia care compared to another study magnitude of satisfaction very low. Regular study and intervention should do every time to increase patient satisfaction. Highlights: Administering regional anesthesia increase patient satisfaction compared to general anesthesia. Pain after surgery leads to patient dissatisfaction. Patient developing nausea and vomiting more dissatisfied than did not develop nausea and vomiting. Decreasing duration of surgery increase satisfaction.